Phase I trial of the mTOR inhibitor everolimus in combination with multi‐agent chemotherapy in relapsed childhood acute lymphoblastic leukemia. Issue 7 (30th March 2018) - Place, Andrew E.; Pikman, Yana; Stevenson, Kristen E.; Harris, Marian H.; Pauly, Melinda; Sulis, Maria‐Luisa; Hijiya, Nobuko; Gore, Lia; Cooper, Todd M.; Loh, Mignon L.; Roti, Giovanni; Neuberg, Donna S.; et al.
Abstract: Background: We sought to determine the feasibility of co‐administering everolimus with a four‐drug reinduction in children and adolescents with acute lymphoblastic leukemia (ALL) experiencing a first marrow relapse. Procedure: This phase I study tested everolimus with vincristine, prednisone, pegaspargase and doxorubicin in patients with marrow relapse occurring >18 months after first complete remission (CR). The primary aim was to identify the maximum tolerated dose of everolimus. Three dose levels (DLs) were tested during dose escalation (2, 3, and 5 mg/m 2 /day). Additional patients were enrolled at the 3‐ and 5 mg/m 2 /day DLs to further evaluate toxicity (dose expansion). Results: Thirteen patients enrolled during dose escalation and nine during dose expansion. During dose escalation, one dose‐limiting toxicity occurred (grade 4 hyperbilirubinemia) in six evaluable patients at DL3 (5 mg/m 2 /day). The most common grade ≥3 adverse events were febrile neutropenia, infections, transaminitis, hyperbilirubinemia, and hypophosphatemia. Two of the 12 patients treated at DL3 developed Rothia mucilaginosa meningitis. Nineteen patients (86%) achieved a second CR (CR2). Of those, 13 (68%) had a low end‐reinduction minimal residual disease (MRD) level (≤10 −3 by polymerase chain reaction–based assay). The CR2 rate for patients with B‐cell ALL treated at DL3 (n = 12) was 92%; 82% of these patients had low MRD. Conclusions: Everolimus combined with four‐drug reinduction chemotherapy was generally well tolerated and associated with favorable rates of CR2 and low end‐reinduction MRD. The recommended phase 2 dose of everolimus given in combination with a four‐drug reinduction is 5 mg/m 2 /day. This promising combination should be further evaluated in a larger patient cohort.